Anatomical and Morphological Variations in Supernumerary Third Head of Biceps Brachii Muscle in Human Cadavers and its Clinical Significance - Roma Patel; Meghana Joshi; Jagdish Soni; Vasant H Vaniya (International Journal of Anatomy Radiology and Surgery, 2023)
Introduction: The biceps brachii muscle takes its name from its two proximally attached ‘heads’. On rare occasions, an anomalous third head arises from the superomedial part of the brachialis and is attached to the bicipital aponeurosis and the medial side of the tendon of insertion. The slip frequently descends in front of and behind the brachial artery and often causes compression of the median nerve or brachial artery. Aim: To calculate incidence of the supernumerary third head of the biceps brachii along with its incidence, anatomical and morphological variations to establish its clinical significance. Materials and Methods: The observational study was conducted in Department of Anatomy, Dr. Kiran C Patel Medical College and Research Institute, Bharuch, Gujarat, India, from October 2021 to September 2022. It included 32 cadaveric upper limbs- 16 right-sided and 16 left-sided. The morphometric measurements were done with the use of digital vernier caliper. The findings were photographed and recorded and the mean and standard deviation were hereby presented and analysed by Statistical Package for Social Sciences (SPSS) version 19.0. Results: The biceps brachii was constituted of supernumery third head in three (9.375%) limbs, one on the right and two on the left-side. In all cases, third head arose from the anteromedial aspect of the mid-humeral shaft; medial to the brachialis and inserted together with the other two heads of the biceps into bicipital aponeurosis and radial tuberosity. The mean length and mean width of the supernumerary head was measured as 141.16±43.63 mm, 25.22±4.99 mm, respectively. A significant difference was not found when compared for symmetrical sides. Conclusion: Three specimen of upper limb were observed with distinct occurrence for the third head with the incidence of 9.37% and predominance on the left-side. In case of various arm surgical procedures knowledge can be used to avoid injuries.